STUDENTS’ VOICES OF THE IMPLEMENTATION OF ONLINE LEARNING DURING THE PANDEMIC OF COVID-19 - Muna Nabilah; Afrianto Daud; M. Syarfi M. Syarfi (International Journal of Educational Best Practices, 2022)
The pandemic of Covid-19 has massively switched education delivery in the world from face-to-face learning to online learning. This qualitative study aimed to investigate students’ voices of the implementation of online learning during the pandemic of Covid-19 in higher education context. There were eight students of English Study Program Universitas Riau involved in this study selected using the purposive sampling technique. Data were collected using semi-structured interviews and documentation. The participants’ voices were thematically analysed in terms of their learning participation, accessibility, material and assignment delivery of the online learning. This study found that the students view online learning as learning experiences that bring both benefits and challenges. Students perceive online learning is a good choice to prevent the spread of coronavirus and a good time to improve their digital skills, but they were not really enthusiastic about its implementation. There are four major obstacles they faced, such as internet access, monotonous teaching method, limited interaction, and ineffective material and assignment delivery. The findings imply that online learning delivery in Indonesia still needs more improvement for better performance in the future.